PENGARUH MINAT, MOTIVASI BELAJAR DAN KEMAMPUAN LITERASI TERHADAP HASIL BELAJAR PADA SEKOLAH MENENGAH KEJURUAN - Nur Intan Baharsyah; Aisyah; Samnur (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
Learning is a process of changing human behavior for the better. In the school environment, these changes can be seen through learning outcomes, where the implementation to achieve these learning outcomes is influenced by various factors including interest and motivation to learn. The purpose of this study was to determine whether interest and motivation to study partially or simultaneously affect the learning outcomes of Vocational High School students. This type of research is a literature review. The samples are 10 international and national journals. Article and journal data collection techniques. The research method used is the journal review method, using Google Scholar. This research was conducted by collecting various articles supporting national and international journals. The criteria for scientific articles used as data are in the form of scientific articles sourced from journals that are updated in the last 5 years. Data collection techniques in this study were carried out by collecting various supporting articles, namely several national journals and 10 international journals.